A Secretaria dos Negócios do Oeste - SNO : as ações do estado no desenvolvimento regional catarinense (1963-1992) - Cassol, Evaldo (2007)
This study aims to identify the reasons which competed for creation, implantation and operation of Secretaria de Estado dos Negócios do Oeste SNO, as well as to analyze the role of the State, the actions developed by SNO as well as its main characteristic, and the factors that competed for its extinction. Secretaria de Estado dos Negócios do Oeste was created by Celso Ramos Government, through the Law number 3.283 on august 17, 1963 and implanted in December 1, 1963, including the area of ancient Chapecó, which was competed by Republic Argentina, and later by the States of Santa Catarina and Paraná. This region belonged to the Território Nacional do Iguaçu from 1943 to 1946. Secretaria dos Negócios do Oeste started because of the lack of support by the State of Santa Catarina, and also because of the movement to start a new State, Iguaçu State, in 1962. The Governor of the State Vilson Pedro Kleinubig wiped SNO out in 1992. It was justified because SNO had already accomplished its role in that area.